Marine bacterial richness increases towards higher latitudes in the eastern Indian Ocean. Issue 1 (20th December 2017) - Raes, Eric J.; Bodrossy, Levente; van de Kamp, Jodie; Bissett, Andrew; Waite, Anya M.
Abstract: We investigated the bacterial community structure in surface waters along a 2500 km transect in the eastern Indian Ocean. Using high throughput sequencing of the 16S rRNA gene, we measured a significant latitudinal increase in bacterial richness from 800 to 1400 operational taxonomic units (OTUs) (42% increase; r 2 = 0.65; p < 0.001) from the tropical Timor Sea to the colder temperate waters. Total dissolved inorganic nitrogen, chlorophyll a, phytoplankton community structure, and primary productivity strongly correlated with bacterial richness (all p < 0.01). Our data suggest that primary productivity drives greater bacterial richness. Because, N2 ‐fixation accounts for up to 50% of new production in this region we tested whether higher N2 ‐fixation rates are linked to a greater nifH diversity. The nifH diversity was dominated by heterotrophic Alphaproteobacteria, Betaproteobacteria, and Gammaproteobacteria. We did not find any mechanistic links between nifH amplicon data, bacterial richness, and primary productivity due to the overall low nifH evenness in this region.